2016
DOI: 10.1155/2016/2092084
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia and Right-to-Left-Shunt in Patient with Antiphospholipid Syndrome: A Case Report with Multimodality Imaging Findings and Literature Review

Abstract: This is a case report of an extremely rare cause of superior vena cava syndrome with systemic-to-pulmonary venous shunts, illustrated using different imaging modalities with successful SVC and IVC dilatation and stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Another rare collateral pathway that is described in case reports is the SPVS [13-15]. Upon review of the literature, we found 2 cases of SVC/IVC obstruction with SPVS [16, 17], but in those cases, the patient had also BCS, while our patient had obstruction of the infrahepatic part of the IVC only (Fig. 3, 3, 4).…”
Section: Discussionmentioning
confidence: 69%
“…Another rare collateral pathway that is described in case reports is the SPVS [13-15]. Upon review of the literature, we found 2 cases of SVC/IVC obstruction with SPVS [16, 17], but in those cases, the patient had also BCS, while our patient had obstruction of the infrahepatic part of the IVC only (Fig. 3, 3, 4).…”
Section: Discussionmentioning
confidence: 69%
“…Very limited data on the incidence of combined SVC and IVC occlusion have been published. There are few case reports that have been published documenting that this has occurred in patients with known hypercoagulable states including prothrombin gene mutation G20210A and APLS [5,6].…”
Section: Discussionmentioning
confidence: 99%